Estimativa da performance térmica de Cycloneda sanguinea L. (Coleoptera: Coccinelidae) utilizando modelos lineares e não lineares - Pachú, Jéssica Karina da Silva (2017)
Understanding the life cycle of insects and their relation to environmental factors such as temperature is essential for the optimization of pest control programs. However, information that considers insect survival and development rates together is incipient. The assessment of these rates concomitantly may reveal the performance in terms of viability and speed of development in a given environmental condition. The insect development rate is often estimated using degree-day-based models, however, nonlinear models have been shown to be more adequate in estimating these rates because they are more realistic and still provide maximum and optimal development temperatures. Thus, the present study estimated the maximum performance of Cycloneda sanguinea L. (Coleoptera: Coccinelidae) as a function of temperature using a linear model, and described the relationship between predator developmental rates and temperature using nonlinear models. The maximum performance was estimated by derivative of the logistic equation. The best models for describing larval phase development rates at different temperatures are the Analytis and Brière models, while Sharpe & DeMichele and Brière are more suitable for the pupa stage of C. sanguinea. For males the estimated temperature that caused the maximum performance was 31°C for the 1st and 2nd instar, for the third and fourth instars the predicted temperature is 28.9 and 27.3oC, respectively. Regarding the females, the temperature that favored the maximum rate of development and survival was 31°C for the first three instars and 27°C to 4th instar. It was evidenced that besides the effect of temperature dependence the performance of the individuals varies according to stage of development and sex of the individuals. With this information it will be possible to better base the multiplication and release programs of C. sanguinea, accurately controlling the speed of development in the laboratory or even scheduling the most favorable times for its release.